Model Project Based Learning (PjBL) dalam Pembelajaran Daring di Sekolah Dasar - Zunita Novi Fithriani; Sumarwiyah Sumarwiyah; Mila Roysa (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to describe the application of the Project Based Learning (PjBL) learning model in online learning at SD Gemiring Lor 01.This study uses a qualitative research type that will be carried out at SD N 01 Gemiring Lor, Nalumsari District, Jepara Regency. The subjects of this study were class teachers and several third grade students at SD N 01 Gemiring Lor. The data in this study were obtained from the results of interviews conducted with research informants. The data analysis technique used is qualitative data. The data collection method used is observation, interviews, and documentation. Checking the validity of the data using credibility, transferability, dependability, confirmability. Data were analyzed using data reduction, data presentation, and drawing conclusions.The results show that the PjBL model can be implemented in online learning in groups. Students who do not have cell phones can be together with friends who have cellphones when working on assignments in groups. In addition, students who do not understand the material can ask their friends when group learning takes place.